Observation of Clinical Efficacy of Anisodamine and Chlorpromazine in the Treatment of Intractable Hiccup after Stroke. - Wang, Jing; Zhu, Qinghua; Zhang, Shuyan; Wen, Lisha; Wang, Li (BioMed Research International, 2022)
Objective. This study is aimed at investigating the clinical efficacy of anisodamine combined with chlorpromazine on intractable hiccups after stroke. Methods. 150 patients admitted to Affiliated Hospital of the Hebei University of Engineering from 2017 to 2021 were selected as the research objects, all of which received the computed tomography (CT) examination. During CT examination, intelligent algorithms were used to segment the images. An unsupervised multilayer image threshold segmentation algorithm was proposed by using Kullback-Leibler (K-L) divergence and the modified particle swarm optimization (MPSO) algorithm. All patients were divided into three groups, with each group of 50 patients. Patients in the control group (group A) took the calcium tablets, vitamin C tablets, and vitamin B1 tablets orally. Patients in the control group (group B) received the acupoint injection of anisodamine, and those in the observation group (group C) received the acupoint injection of anisodamine combined with chlorpromazine. The therapeutic effect and patient satisfaction of the three groups were compared. Results. The two-dimensional (2D) K-L divergence was applied for the multilayer segmentation of images, which was helpful to obtain accurate images. The MPSO algorithm was adopted to reduce the computational complexity. The total efficiency of group C was 98%, that of group B was 56%, and that of group A was 22%. The total efficiency and satisfaction rate of group C were signally better than those of group A and group B (P < 0.05). Conclusion. The combination of 2D K-L divergence and MPSO algorithm could improve the accuracy of multilayer image segmentation and CT imaging. Acupoint injection of anisodamine combined with chlorpromazine had better efficacy than the injection of anisodamine alone for the treatment of intractable hiccups after stroke, with high safety and clinical promotion value.